From the history of the resistance and the national liberation movement in Iraq 1914-1920 « Reviews in the National Memory » - abbou, Najat (The Algerian Historical Journal, 2026)
This study aims to present a summary of the political developments that Iraq witnessed in the last years of the Ottoman rule, by tracing the path of the revolutionary liberation movement in Iraq, and deducing the most important factors that contributed to its development, with a mention of the most important means adopted in the Iraqi national struggle, and their contribution to fueling the masses Popular people to fight the foreign enemy, and their adherence to the principle of freedom and independence. We have concluded that Iraq witnessed important historical events that constituted a turning point in its political history, the most prominent of which was the beginning of the spread of the Arab nationalist movement, so the Iraqis became among the most important supporters and defenders of Arab unity, which contributed to advancing the movement of the national struggle, and their rejection of the British occupation, so they did not hesitate to declare the armed revolution , which became one of the most important revolutions in the Arab world in that era.